Contemporary Dimensions of Omani Jewelry from the Perspective of women in current generations (Al-Academy, 2025)
Objectives: The study aims to identify the contemporary dimensions of Omani jewelry from the perspective of women in current generations in Oman and to clarify the ability of jewelry designers to preserve the authenticity of Omani jewelry while keeping pace with modern development and creativity. It examines also the intellectual and social trends in designing contemporary jewelry which are compatible with the reality of its wearers.Methods: Quantitative method is used to collect data about the contemporary dimensions of Omani jewelry, through semi-structure interviews with Omani women from different governorates of the Sultanate of Oman.  It collected (150) interviews, but (56) interviews were selected as a deliberate sample with women who have experience and knowledge of the contemporary dimensions of jewelry from different governorates, whose ages range between (15-40 years).Results: The results showed the contemporary dimensions of Omani jewelry are formed by its reflection of women lifestyle, the influence of artistic movement, fashion trends and financial independence of women. Moreover, cultural critical trends in jewelry design were compatible with the reality of its wearers. The structuralism emphasized the relationship of the collector with the jewelry as product, which was achieved in both the material and moral factors.Conclusions: The study conclude that values ​​of contemporary dimensions of jewelry are not fixed, but rather evolve with the cultural, social and economic changes that affect each generation which impact on how it appreciates jewelry.Keywords: Omani jewelry identity, contemporary design, fashion trends, social trends, structuralism.